1984
DOI: 10.1161/01.hyp.6.4.454
|View full text |Cite
|
Sign up to set email alerts
|

Rat thymocyte sodium transport. Effects of changes in sodium balance and experimental hypertension.

Abstract: SUMMARY The wide range of membrane electrolyte transport abnormalities associated with experimental, genetic, and essential hypertension may either reflect an underlying global change in the cell membrane or may be directly related to the underlying disturbance that causes hypertension or to changes in sodium balance. To investigate this further, we studied sodium transport and intracellular electrolyte composition in the thymocytes of normal rats undergoing salt loading or depletion, and in rats with renovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In contrast, the same investigators could detect neither a change in intracellular sodium content nor pump activity in one-kidney, one clip hypertensive rats. 215 The DOCA salt-sensitive rats exhibit a decrease in intracellular sodium content, though their efflux rate constants are similar. Other observers have demonstrated reduction in the Na,KATPase activity of this model.…”
Section: Defects Of Sodium Metabolism In Animalsmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, the same investigators could detect neither a change in intracellular sodium content nor pump activity in one-kidney, one clip hypertensive rats. 215 The DOCA salt-sensitive rats exhibit a decrease in intracellular sodium content, though their efflux rate constants are similar. Other observers have demonstrated reduction in the Na,KATPase activity of this model.…”
Section: Defects Of Sodium Metabolism In Animalsmentioning
confidence: 97%
“…214 Less is known about intracellular sodium content in salt-induced or volume-dependent hypertensive models. 196 - 215 In normal rats fed high sodium diets to induce volume expansion, there is no change in intracellular sodium. 215 Nor is there any change in thymocyte sodium content in two-kidney, one clip hypertension, even though Na,K-ATPase is reduced.…”
Section: Defects Of Sodium Metabolism In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jones et al l6 reported that T lymphocytes from spontaneously hypertensive rats exhibited higher sodium content and a decrease in the rate constant for total sodium efflux (active and passive combined) as compared with normotensive controls. Bradlaugh et al, 17 however, did not find a significant difference in sodium rate constants (active or passive) of lymphocytes from spontaneously hypertensive rats and normotensive rats. These investigators have presented evidence that suggests that the decreased sodium efflux rate constant observed by Jones et al 16 is attributable to age of the rat rather than to the blood pressure elevation of spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 87%
“…14 Although, as far as we know, there have not been any reported studies of peripheral blood lymphocytes of rats, Jones et al 16 and Bradlaugh et al 17 have examined sodium content and transport in thymocytes (T lymphocytes) derived from the rat thymus gland. Jones et al l6 reported that T lymphocytes from spontaneously hypertensive rats exhibited higher sodium content and a decrease in the rate constant for total sodium efflux (active and passive combined) as compared with normotensive controls.…”
Section: Discussionmentioning
confidence: 99%